How Artificial Intelligence Can Help Advance Post-Secondary Learning in Emerging Markets - Makala, Baloko (International Finance Corporation, Washington, DC, 2021)
Tertiary and vocational learning is widely recognized as critical for all countries’ economic success. While progress has been made toward achieving the fourth United Nations’ (UN) sustainable development goal (SDG 4) by 2030 - ensure inclusive and equitable quality education and promote lifelong learning for all - a 2019 UN report shows that some 750 million adults are functionally illiterate. These statistics illustrate the enormous challenge of adequately preparing the workforce for rapid technological change that will require continual reskilling. Although machines with artificial intelligence are likely to replace millions of workers across the world, artificial intelligence (AI) also has great potential to enable workers to keep up with technological change and remain employable. This note attempts to illustrates how AI can support post-secondary learning across the entire tertiary and vocational education sector in emerging markets.